Proverb: Nearly Spring in a New Hampshire Barn - Randall, Regine (On and Off the Road: Poems of New Hampshire, 2020)
"This poetry anthology, with poems from poets throughout New England and from other states - is a result of Peterborough Poetry Project's second poetry contest. We invited poets, writers, and observers to submit up to three poems about New Hampshire - past, present, future, or fantasy. Forty-eight poems from the contest form this book. The poems are in three different sections by themes: People, Places, and The Wild, but readers may find that several poems have more than one theme. A poem may appear to be about nature, but also our reactions to it. Another poem may appear to be true, but might be pure fantasy. Such is the nature of poetry: read it for the obvious, then read it again to see if more reveals itself"--Back cover
Keywords: dept.cur; literary-poetry

Disconnected in a connected world: improving digital literacies instruction to reconnect with each other, ideas, and texts - Marangell, Joseph; Randall, Régine (Education Sciences, 2025)
This commentary addresses a problem of practice related to student disengagement in technology-rich classrooms, where learners are digitally connected but socially and academically disconnected. Although not an empirical study, the commentary draws on instructional examples from secondary- and graduate-level teaching. The authors examine how digital literacy instruction can strengthen engagement, reading comprehension, and ethical participation in online environments. The article highlights strategies such as the workshop model, multimodal composition, digital content curation, and the use of mentor texts to support critical thinking and collaborative learning. These practices aim to develop students’ analytical skills, awareness of audience, and recognition of their own positionality in digital spaces. Across courses, the authors reflected on increased student engagement when digital tools were used not simply for task completion but to support inquiry, discourse, and authentic creation for real audiences.
Keywords: Comprehension; Computer science; Critical thinking; Digital literacy; Disengagement theory; Linguistics; Literacy; Mathematics education; Pedagogy; Psychology; Reading (process); Reading comprehension; Sociology; Student engagement; Task (project management); dept.cur

Teaching students to write: Arguing against the overuse of argument - Randall, Régine; Mercurio, Mia Lynn (Kappa Delta Pi Record, 2017)
This personal editorial written by two education professors considers the Common Core State Standards and argues against the overuse of argument in the teaching of writing. © Kappa Delta Pi.
Keywords: Common core; Writing; dept.cur; dept.sed

Valuing stuff materials culture and artifactual literacies in the classroom - Randall, Regine; Mercurio, Mia Lynn (Journal of Adolescent & Adult Literacy, 2015)
Recent interest in materials culture and artifactual literacies has helped the authors of this article rethink how they teach preservice and inservice teachers and collaborate with K-12 teachers. Each discipline has its own stuff that can help students understand the products and practices of a field beyond what they might be able to glean from text. To that end, every teacher should see their classroom and content area as a "place for my stuff" because objects speak and communicate more messages through form, color, size, and texture than print alone. © 2015 International Literacy Association.
Keywords: 3-Early adolescence; 4-Adolescence; 5-College/university students; Adolescent/young adult literature; Content analyses; Content literacy; Discussion strategies; Information literacy; Informational text; Instructional strategies; Literary elements; Specific subject areas (math; Strategies; Text types; and materials; art; dept.cur; dept.sed; etc.); methods; teaching strategies; text features

Improving students' academic learning by helping them access text - Ben-Avie, Michael; Randall, Régine; Dunne, Diane Weaver; Kelly, Chris (Recent Advances in Assistive Technologies to Support Children with Developmental Disorders, 2015)
Conventional methods of addressing the needs of students with print disabilities include text-to-speech services. One major drawback of text-to-speech technologies is that computerized speech simply articulates the same words in a text whereas human voice can convey emotions such as excitement, sadness, fear, or joy. Audiobooks have human narration, but are designed for entertainment and not for teaching word identification, fluency, vocabulary, and comprehension to students. This chapter focuses on the 3-year pilot of CRISKids; all CRIS recordings feature human narration. The pilot demonstrated that students who feel competent in their reading and class work tend to be more engaged in classroom routines, spend more time on task and demonstrate greater comprehension of written materials. When more demonstrate these behaviors and skills, teachers are better able to provide meaningful instruction, since less time is spent on issues of classroom management and redirection. Thus, CRISKids impacts not only the students with print disabilities, but all of the students in the classroom.
Keywords: dept.cur